DEVELOPMENT OF AUDIO-VISUAL LEARNING MEDIA BASED ON THE CAPCUT APPLICATION TO ENHANCE JUNIOR HIGH SCHOOL STUDENT'S LEARNING MOTIVATION - Patibang, Rike Trisanti; Paat, Meike; Rungkat, Jovialine Albertine; Warouw, Zusje Wiesje Merry; Rampengan, Mercy Maggy Franky; Mokalu, Yohanes Bery (Universitas Bhinneka PGRI, 2025)
This study aims to develop audio-visual learning media based on the CapCut application to enhance junior high school students' learning motivation on the topic of the human digestive system. The method employed is Research and Development (RD) using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) to produce learning media that are valid, practical, and effective. The research subjects were eighth-grade students at SMP Negeri 1 Tombulu. Validation results indicated that the media were deemed highly valid by both content experts (94%) and media experts (96%). The practicality of the media was also rated highly, with teacher responses at 96%, small group trials at 97.53%, and large group trials at 96.06%. The effectiveness of the media was evidenced by a significant increase in students’ learning motivation, with an N-Gain score of 0.95 or 94.57%, and an improvement in learning outcomes with an N-Gain of 0.79 or 79%. This media integrates animation, text, audio, and interactive video, thereby facilitating engaging delivery of the material. The study demonstrates that CapCut-based media can serve as an innovative solution to improve the quality of science learning at the junior high school level.